CRITERIA FOR DETERMINING INDUSTRIAL SIGNIFICANCE OF COAL RESERVES: DOMESTIC CLASSIFICATIONS VS JORC - Rudko, G.; Kurylo, M.; Bala, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Main objective of the study is analysis and systematization of the criteria by which industrial significance and value of coal reserves are determined in domestic and international practice. We analyzed the example of coal deposit reserves' structure. These reserves were calculated according to previous years' cut-off parameters with allocation of balance and off-balance reserves taking into account differences in coal quality and mining technical conditions. Their classification is given in form of a three-digit code in accordance with the Instruction for Application of the Classification of Mineral Reserves and Resources of the State Subsoil Fund to coal deposits. Their relation with groups of reserves and resources was determined by the Australian Guidelines for Estimation and Classification of Coal Resources. Parameters for quality and quantity assessments of coal reserves have been analyzed. Industrial significance of the deposit was determined taking into account the total volumes of coal in the subsoil and those volumes that can be extracted profitably with implementation of a specific mining project. It was defined that coal reserves recalculating using the JORC standards form the smallest quantities of reserves that have industrial importance. These are categories of Proved and Probable Coal Reserves. These groups require a positive assessment of all modifying factors and availability of a mining project to which they are applied. A particular feature of the Australian Guidelines is availability of the category Inventory Coal, which can be conditionally compared with domestic categories of resources and conditionally-balance reserves or those reserves groups for which industrial value has not been determined. This category is used for full assessment of state's resource base in "non-public" reporting for strategic planning purposes. Using the Classification of Mineral Reserves and Mineral Resources of the State Subsoil Fund also allows including groups of conditionally balanced and off-balance reserves in the structure of reserves. Such approaches provide an opportunity for detailed account of sufficiently proven coal reserves, which qualitatively meet the requirements of the balance. In domestic standards Proved and Probable Coal Reserves groups correspond to balance reserves with different degrees of geological study, allocated within the design contours of mine workings. As a rule they form a quantity of industrial reserves. At the same time, the domestic classification makes it possible to take into account other quantities of explored reserves and inferred resources that form the possibility of future growth. The practical significance of this analysis is to facilitate geological and economic evaluation of coal deposits, which are explored in different standards of geological study.
Keywords: commercial significance; coal reserves; classification of reserves and resources; international standards